Anti-Aging Potential of Phytoextract Loaded-Pharmaceutical Creams for Human Skin Cell Longetivity - Jadoon, Saima (Oxid Med Cell Longev, 2015)
The exposure to ultraviolet radiations (UVR) is the key source of skin sunburn; it may produce harmful entities, reactive oxygen species (ROS), leading to aging. The skin can be treated and protected from the injurious effects of ROS by using various pharmaceutical formulations, such as cream. Cream can be loaded with antioxidants to quench ROS leading to photo-protective effects. Moreover, modern medicines depend on ethnobotanicals for protection or treatment of human diseases. This review article summarizes various in vivo antioxidant studies on herbal creams loaded with phyto-extracts. These formulations may serve as cosmeceuticals to protect skin against injurious effects of UVR. The botanicals studied for dermatologic use in cream form include Acacia nilotica, Benincasa hispida, Calendula officinalis, Camellia sinensis, Camellia sinensis, Nelumbo nucifera, Capparis decidua, Castanea sativa, Coffea arabica, Crocus sativus, Emblica officinalis Gaertn, Foeniculum vulgare, Hippophae rhamnoides, Lithospermum erythrorhizon, Malus domestica, Matricaria chamomilla L., Moringa oleifera, Morus alba, Ocimum basilicum, Oryza sativa, Polygonum minus, Punica granatum, Silybum marianum, Tagetes erecta Linn., Terminalia chebula, Trigonella foenum-graecum, and Vitis vinifera. The observed anti-aging effects of cream formulations could be an outcome of a coordinating action of multiple constituents. Of numerous botanicals, the phenolic acids and flavonoids appear effective against UVR-induced damage; however the evidence-based studies for their anti-aging effects are still needed.